Level 3 Assets: Booking Profits and Concealing Losses - Milbradt, Konstantin (Review of Financial Studies, 2012)
[Fair value accounting forces institutions to revalue inventory whenever a transaction occurs. An institution that faces a balance sheet constraint may have incentives to suspend trading in Level 3 assets (traded on opaque over-the-counter markets) in order to avoid such marking-to-market. This keeps the book valuation artificially high, relaxing the balance sheet constraint. But, the institution loses direct control of the risk of its position. Solving this "real options" problem, the institution will report profits as they occur but delay reporting losses. A regulator trying to control risk imposes fines for balance sheet manipulation and capital requirements. Both these tools can increase risk-taking and balance sheet manipulation. Audits in comparision generally decrease risk-taking but may be costly to the regulator. The model provides predictions on the distribution of a bank's trading gains in illiquid markets.]